HUBUNGAN MORFOMETRI AMBING TERHADAP PRODUKSI SUSU KAMBING PERANAKAN ETAWA - MUHAMMAD HAMAMI, 061411131119 (2018)
Needs of animal protein will continuously rise along with increasing population in Indonesia. This require effort to increase animal protein consumtion. Milk is one of an animal protein that produced by dairy cattle. Apart of dairy cattle, raising dairy goat of Peranakan Etawa (PE) is an alternative to produce milk in Indonesia. It is capable to supply the high necessary of milk in Indonesia. Many factors can influence milk production. Genetic, age, udder size, parity period, lactation period and feed are the important part to decided milk production. The research aimed to study the correlation of udder morphometry toward milk production of Peranakan Etawa dairy goats in UPT PT & HMT Singosari Malang. The sample was taken from 20 samples of ewes. Milk yield was taken and recorded daily during the study period, the measurement of udder morphometry based on udder circumference, high of udder, teat circumference and high of teat are using a rope that converted into a tape measure, the samples were taken and recorded four repetitions during study period. Data has been collated and analyzed using multiple regression analysis with SPSS 23 software. The result showed significant coefficients of udder circumference 0,038 (p<0,05), high of udder 0,712 (p>0,05), teat circumference 0,631 (p>0,05) and high of teat 0,259 (p>0,05). So only udder circumference has a correlation with milk production, and this is also shown that udder circumference has a correlation coefficient 0,79 which means it has very strong correlation with milk production.